ANALISIS RASIO KEUANGAN UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Manurung, Juliana; Munthe, Kornel (UNIKA Santo Thomas, 2019)
This study aims to predict financial distress through the variable lancer ratio, return on assets and debt to equity ratio since 1, 2 and 3 years before it occurs in manufacturing companies listed on the Indonesia Stock Exchange. The study population was all manufacturing companies listed on the Indonesia Stock Exchange, and by using purposive sampling, a sample of 66 companies was obtained. The data analysis method used is logistic regression. The results showed the current ratio variable, return on assets and debt to equity ratio, together had a significant effect on the probability of financial distress for one, two and three years before it occurred in the manufacturing companies listed on the Indonesia Stock Exchange since one, two and three before it occurs at Î± = 5 percent. The level of prediction accuracy of the effect of financial ratio information on the probability of financial distress on companies that have been listed on the Indonesia Stock Exchange since one, two and three years before experiencing financial distress occurred respectively was 97.0 percent, 77.3 percent and 74.2 percent. The current ratio variable and the debt to equity ratio partially do not significantly influence the probability of financial distress for one, two and three years before it occurs, whereas the debt to equity ratio partially has a positive and significant effect on financial distress for one, two and three years before it occurs in companies that have been listed on the Indonesia Stock Exchange.